A Shortened Version of the Suicide Cognitions Scale for Identifying Chronic Pain Patients at Risk for Suicide. Issue 3 (18th June 2016) - Bryan, Craig J.; Kanzler, Kathryn E.; Grieser, Emily; Martinez, Annette; Allison, Sybil; McGeary, Donald
Abstract: Objective: Research in psychiatric outpatient and inpatient populations supports the utility of the Suicide Cognitions Scale (SCS) as an indicator of current and future risk for suicidal thoughts and behaviors. Designed to assess suicide‐specific thoughts and beliefs, the SCS has yet to be evaluated among chronic pain patients, a group with elevated risk for suicide. The purpose of the present study was to develop and test a shortened version of the SCS (the SCS‐S). Study Design: A total of 228 chronic pain patients completed a battery of self‐report surveys before or after a scheduled appointment. Setting: Three outpatient medical clinics (pain medicine, orofacial pain, and clinical health psychology). Methods: Confirmatory factor analysis, multivariate regression, and graded item response theory model analyses. Results: Results of the CFAs suggested that a 3‐factor solution was optimal. A shortened 9‐item scale was identified based on the results of graded item response theory model analyses. Correlation and multivariate analyses supported the construct and incremental validity of the SCS‐S. Conclusions: Results support the reliability and validity of the SCS‐S among chronic pain patients, and suggest the scale may be a useful method for identifying high‐risk patients in medical settings.